2021
DOI: 10.1021/acs.energyfuels.1c00169
|View full text |Cite
|
Sign up to set email alerts
|

H3PO4-Assisted Synthesis of Apricot Shell Lignin-Based Activated Carbon for Capacitors: Understanding the Pore Structure/Electrochemical Performance Relationship

Abstract: The main focus of this study was to give an idea for the value added from lignin and further understand the pore structure/electrochemical performance relationship. A case study of using H3PO4-assisted apricot shell lignin (ASL) was used to synthesize apricot shell lignin-based activated carbon (AAC) for capacitors. Considering performance and cost, the activation temperature of ASL was 550 °C. The as-obtained AAC-3 possesses the highest specific surface area (1474.82 m2/g) and the highest mass-specific capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Curves with a hysteresis loop upon moderate pressure indicate the existence of mesopores in samples. In the high-pressure range, the curves rise sharply, meaning that there are macropores in samples . The porosity hierarchy structures of PC-0 and PC-1 are depicted in Figure a.…”
Section: Resultsmentioning
confidence: 98%
“…Curves with a hysteresis loop upon moderate pressure indicate the existence of mesopores in samples. In the high-pressure range, the curves rise sharply, meaning that there are macropores in samples . The porosity hierarchy structures of PC-0 and PC-1 are depicted in Figure a.…”
Section: Resultsmentioning
confidence: 98%
“… 29 In reviewing the literature, Li et al 45 indicated the nitrogen content of bamboo biochar detected by element analyzer and XPS being 0.6% and 0.4%, respectively. Wang et al 46 demonstrated the nitrogen content for lignin-derived porous carbon determined by element analyzer and XPS is 0.24% and 0%, respectively. Similarly, Xu et al 29 illuminated the nitrogen content for fiberboard biochar detected by element analyzer and XPS being 3.42% and 2%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…( C ) Specific capacitances at varying applied currents of ZnAC 1 , ZnAC 2 , KAC, and KAC urea . ( D ) Capacitance comparison of the best-performing KAC urea with the reported values in the literature [ 1 , 33 , 52 , 53 , 54 ].…”
Section: Figurementioning
confidence: 99%
“…Carbon-based electrode materials are suitable for energy storage applications because they possess attractive features such as excellent chemical and thermal stability, high electrical conductivity, and a large surface area [ 1 ]. Various carbonaceous materials—such as activated carbon (AC), carbon nanotubes (CNTs), carbon aerogels, graphene, ordered mesoporous carbon, carbon composites, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation